In vitro activity of Bay 09867, a new quinoline derivative, compared with those of other antimicrobial agents. - Wise, R (1983)
The in vitro activity of Bay 09867, a new quinoline derivative, was compared with those of norfloxacin, nalidixic acid, ceftazidime, cefaclor, cefuroxime, gentamicin, and other antimicrobial agents, when appropriate, against 410 recent clinical isolates. The minimal inhibitory concentrations of Bay 09867 for 90% of Enterobacteriaceae, Pseudomonas aeruginosa, Haemophilus influenzae, Neisseria gonorrhoeae, streptococci, Staphylococcus aureus, and Bacteroides fragilis strains were between 0.008 and 2 micrograms/ml. Bay 09867 was considerably more active against the gram-negative bacteria tested than were other agents tested. Gentamicin-resistant Enterobacteriaceae, P. aeruginosa, and methicillin-resistant S. aureus were highly susceptible to Bay 09867. Strains less susceptible to nalidixic acid and norfloxacin tended to be less susceptible to Bay 09867. The protein binding of Bay 09867 was about 20%.